PENGEMBANGAN BUKU ILUSTRASI MODIFIKASI PERILAKU ASERTIF: UPAYA PREVENTIF PELECEHAN SEKSUAL PADA ANAK - Andriani, Opi; Zunarti, Rita; Afri Yanti Daulay, Nur (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The urgency of this research is to reduce the intensity of victims of sexual harassment that occurs in elementary school-age children by increasing assertive behavior through the application of behavior modification modeling techniques by mothers who are guided by illustration books that are specially designed to be easy to understand and apply by family members, especially mothers. This research aims to develop the book